Identifying targets for interventions to support public use of face coverings. Issue 1 (1st September 2022) - Armitage, Christopher J.; Keyworth, Chris; Gartland, Nicola; Coleman, Anna; Fishwick, David; Johnson, Sheena; van Tongeren, Martie
Abstract: Objectives: Interventions to promote the wearing of face coverings if required in the future can only be developed if we know why people do or do not wear them. Study aims were, therefore, to assess public adherence to wearing face coverings to reduce transmission of SARS‐CoV‐2 and to gauge why people were or were not wearing face coverings in work, public transport, and indoor leisure settings. Design: Cross‐sectional survey. Methods: 10, 622 adults (25 January–6 February 2022) who were representative of the UK population were asked about their (a) wearing of face coverings in work, public transport, and leisure settings; (b) sociodemographic characteristics; and (c) perceptions of capabilities, opportunities, and motivations ("COM‐B"). Data were analysed descriptively, using within‐participants ANOVA and multiple linear regression. Results: Participants reported mostly wearing face coverings in public transport settings (>80%), but substantially less in work (<50%) and leisure (<30%) contexts. Perceptions of capabilities, opportunities, and motivations to wear face coverings were consistently associated with the actual wearing of face coverings across the three settings, but there were marked deficits in automatic motivation and social opportunity. People living in England, describing themselves as White, and men were least likely to wear face coverings. Conclusions: Interventions targeted at men, people living in England, and those describing themselves as White that focus on increasing capabilities, providing greater opportunities and boosting motivations are suggested to promote the wearing of face coverings, with particular focus on addressing automatic motivation and social opportunity.